A SEMANTIC ANALYSIS OF ENGLISH COPY RAISING CONSTRUCTIONS - Doran, Diane (My University, 2015)
This thesis is an investigation of the structural and formal semantic properties of copy raising constructions in English, as well as their expletive counterparts. The first main claim is that contrary to what has been previously assumed, the perceiver of the event (i.e. the Pgoal in Asudeh & Toivonen's 2012 terms) is an obligatory syntactic and semantic argument of the matrix verb. I argue that the identification of the Pgoal is not left to pragmatics, but rather that is represented as a silent pronoun in the structure: one that picks up a logophoric antecedent. The result of this is that the material in the embedded clause is semantically interpreted with respect to the Pgoal's perspective. The second major claim of the thesis is that this perspective-sensitivity is most appropriately captured using a modal semantic framework (Kratzer, 1977, 1981 von Fintel & Heim, 2002). Specifically, I argue that each of the different copy raising verbs encodes a different accessibility relation between possible worlds or situations, while the Pgoal's information state provides the relevant domain of worlds. Using these insights, I propose truth conditions for these constructions, which ultimately are sensitive to a kind of stereotypical ordering, and account for inter-speaker variability. Finally, I discuss the anomalous class of copy raising constructions with non-thematic subjects, and argue that overlapping discourse functions may have resulted in a shift away from modal semantics in these cases.
Keywords: copy raising; modal semantics; evidentiality; perspective-sensitivity; truth conditions; logophoricity; situation semantics